2004
DOI: 10.1097/01.cmr.0000136711.75287.55
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide and interferon-alpha in metastatic melanoma: a phase II study of the Italian Melanoma Intergroup

Abstract: Temozolomide (TMZ) is a new oral alkylating agent which has proven to be as active as dacarbazine (DTIC) in the treatment of melanoma, but with a lower toxicity. A multicentric phase II trial was conducted in an out-patient setting to determine the therapeutic activity and safety of TMZ in combination with interferon-alpha (IFN-alpha). From June 2000 to July 2001, 41 patients were recruited to receive TMZ 200 mg/m orally on days 1-5 every 28 days and with 5 MU IFN-alpha subcutaneously three times a week, conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Eleven of the trials were published as full reports [8,10,12,13,15,16,19,20,24,26,28], while 10 were available only in abstract form [9, 11, 14, 17, 18, 21-23, 25, 27]. Patient characteristics and trial descriptions for those trials are shown in Table 2.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of the trials were published as full reports [8,10,12,13,15,16,19,20,24,26,28], while 10 were available only in abstract form [9, 11, 14, 17, 18, 21-23, 25, 27]. Patient characteristics and trial descriptions for those trials are shown in Table 2.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In addition, phase I or II trials investigating singleagent temozolomide (n ϭ 9) [8 -16], temozolomide plus IFN-␣ (n ϭ 6) [17][18][19][20][21][22], and temozolomide plus thalidomide (n ϭ 6) [23][24][25][26][27][28] were reviewed. Eleven of the trials were published as full reports [8,10,12,13,15,16,19,20,24,26,28], while 10 were available only in abstract form [9, 11, 14, 17, 18, 21-23, 25, 27].…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the response rate of the patients suffering from melanoma treated with DTIC or TMZ remains poor, with median survival durations between 5.3 and 6.7 months (3,4). Treatment combining TMZ with IFN-a can increase median survival to 11.8 months (5). There is, however, no clear rationale for concomitant treatment with IFN and TMZ except the finding that IFNs may cause immunosensitization of the tumor (6).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the combination of IFN with chemotherapy drugs increases the antitumor effects (24)(25)(26). Recently, combined therapy using TMZ and IFN-· has been shown to be quite tolerable in patients with metastatic melanoma (27) and renal cell carcinoma (28). In the present study, we investigated the effects of combined TMZ and IFN-ß in U-87 orthotopic xenograft brain tumor models and the possible mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%